2020
DOI: 10.1109/access.2020.3032186
|View full text |Cite
|
Sign up to set email alerts
|

Review of Recent Progress on Silicon Nitride-Based Photonic Integrated Circuits

Abstract: Silicon photonic devices are being used in the photonics industry over the past three decades has helped in realizing large-scale photonic integrated circuits. Silicon nitride (Si3N4) is another CMOScompatible platform that provides several advantages such as low loss, high optical power tolerance, and broad spectral operation band from visible to infrared wavelengths. Recently, the combination of Si3N4waveguide technology with silicon photonics and III-V materials has opened up new areas in the field of on-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 99 publications
0
33
0
Order By: Relevance
“…Silicon nitride on insulator (SiNOI) waveguide platform, where the insulator here is the silicon dioxide, offers numerous advantages for various applications [ 12 , 13 , 14 , 15 ]. Similar to silicon on insulator (SOI) platform SiNOI is a complementary metal-oxide semiconductor (CMOS) compatible allowing for mass-scale and low-cost fabrication [ 14 , 15 ]. It also allows for monolithic integration with silicon devices and other electronic circuitry [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride on insulator (SiNOI) waveguide platform, where the insulator here is the silicon dioxide, offers numerous advantages for various applications [ 12 , 13 , 14 , 15 ]. Similar to silicon on insulator (SOI) platform SiNOI is a complementary metal-oxide semiconductor (CMOS) compatible allowing for mass-scale and low-cost fabrication [ 14 , 15 ]. It also allows for monolithic integration with silicon devices and other electronic circuitry [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the high price of PICs compared to that of electronic-integrated circuits currently acts as a barrier for its application, scientific interest in this technology is continuously emerging [ 9 ]. Sharma et al [ 10 ] provided an overview of the latest achievements of SiNx-based PICs, highlighting the benefits of these devices such as the small signal loss or the ability to work with wide-wavelength ranges. Frigg et al [ 11 ] found that SiNx thin films deposited by direct current sputtering is able to further decrease the loss, which is attributed to the lack of hydrogen bonds compared to its other chemical vapor deposited counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Si 3 N 4 thermo-optical coe cient is one order of magnitude lower than Si [13], hence Si 3 N 4 based devices are less sensitive to temperature uctuations. Moreover, SiNOI platform has wider transparency range, from visible to mid-infrared, compared to SOI platform [12][13][14][15]. This allows the realization of photonic applications outside the telecom bands, such as integrated optical phased arrays for LIDAR applications [16].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while silicon have large Kerr effect the two-photon absorption (TPA) prevents e cient nonlinear applications. Si 3 N 4 on the other hand, has adequate Kerr nonlinearity and almost zero TPA [14][15]. Thus, SiNOI platform allow for frequency comb as well as supercontinuum generation [17][18], which are essential for high data-rate telecommunications, high-resolution spectroscopy and frequency metrology [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation